INTEGRATING CORPUS CONSULTATION IN LANGUAGE STUDIES - Angela Chambers (Language Learning and Technology, 2005)
Alongside developments in language research, the potential of corpora as a resource in language learning and teaching has been evident to researchers and teachers since the late 1960s. Despite publications which emphasise the benefits of corpus consultation for language learners (Bernardini, 2002; Kennedy & Miceli, 2001), there is little evidence to suggest that direct corpus consultation is coming to be seen as a complement or alternative to consultation of a dictionary, course book, or grammar by the majority of learners. There is thus a need for research to underpin the integration of corpora and concordancing in the language-learning environment.This study begins with an account of published research relating to course design and structure in the area of corpus consultation by language learners. The focus then narrows to the initial training of learners in corpus consultation, using as an example a course involving undergraduate students on several language degree programmes. The results of the students' consultation of the corpora are examined, including choice of search word(s), analytical skills, the problems encountered, and their evaluation of the activity. The results reveal how corpus consultation can complement traditional language-learning resources, while also raising questions concerning its integration in the language-learning environment.